Administrative reasons for farmers’ reluctance to attend agricultural extension activities in the Nineveh Directorate of Agriculture and its affiliated divisions (International Journal of Environmental Sciences, 2025)
The aim of this study was to identify the administrative reasons that drive farmers to refrain from attending agricultural extension activities. It also sought to examine the correlation between the levels of reasons for farmers’ reluctance to attend extension activities organized by the Nineveh Directorate of Agriculture and its affiliated divisions, and each of the following variables: gender, age, educational level, ownership of a means of transportation, engagement in non-agricultural work, living standard, willingness to learn new things, type of agricultural work, and health status.The study specifically focused on the administrative reasons behind this reluctance. A descriptive analytical methodology was used, supported by a field questionnaire involving a sample of farmers. The results revealed that the reluctance is due to a combination of personal, economic, social, organizational, and educational factors. Among the most prominent were the lack of incentives, weak coordination, and insufficient awareness. The findings indicated a significant overall reluctance among farmers to attend extension activities in the Nineveh Directorate of Agriculture, with a level described as moderate tending toward low. The administrative reasons varied in their degree of influence. A statistically significant correlation was found between the levels of reluctance and two variables: educational level and ownership of a means of transportation. Other variables did not show a significant correlation, possibly due to factors such as Type II error or sample selection bias. The researcher provided several key recommendations to the Nineveh Directorate of Agriculture, including: Reorganizing extension programs according to a clear and coordinated schedule, with effective prior notification to farmers. Improving administrative communication between extension agencies and farmers through modern tools such as text messages or mobile applications.